Post-cricoid and Upper Oesophagus Cancers Treated with Organ Preservation Using Intensity-modulated Image-guided Radiotherapy: a Phase II Prospective Study of Outcomes, Toxicity and Quality of Life. Issue 4 (April 2022) - Laskar, S.G.; Sinha, S.; Singh, M.; Mummudi, N.; Mittal, R.; Gavarraju, A.; Budrukkar, A.; Swain, M.; Agarwal, J.P.; Gupta, T.; Murthy, V.; Mokal, S.; et al.
Abstract: Aims: To prospectively examine the outcomes, toxicity and quality of life (QoL) of patients with post-cricoid and upper oesophagus (PCUE) cancers treated with an organ-preservation approach of (chemo)-radiotherapy using intensity-modulated image-guided radiotherapy (IM-IGRT). Materials and methods: This phase II prospective study was conducted at a tertiary cancer centre from February 2017 to January 2020. Forty patients with squamous cell carcinoma of PCUE of stage T1-3, N0-2, M0 were accrued. Gross exolaryngeal extension/dysfunctional larynx were major exclusion criteria. Patients received 63–66 Gy in once-daily fractions using volumetric modulated arc therapy with daily IGRT. Outcome measures included disease-related outcomes, patterns of failure, Radiation Therapy Oncology Group toxicities, feeding tube dependency and QoL. Results: The median follow-up was 22 months. Twenty-six (87.5%) patients had locoregionally advanced disease and 34 (85%) patients received (chemo)-radiotherapy. A complete response was observed in 26 (65%) patients. The 2-year locoregional control, event-free survival and cause-specific survival were 59.6%, 40.2% and 44.8%, respectively. The volume of primary tumour (GTVPvol) exceeding 28 cm 3 had inferior overall survival ( P = 0.005) on univariate analysis. Multivariable analysis showed GTVPvol and positron emission tomography-computed tomography maximum standardised uptake value to be independently predictive for event-free and overall survival. A feeding tube requirement at presentation was seen in 11 (27.5%) patients, whereas long-term feeding tube dependency at 6 months was seen in 10 (37%) patients. For QoL, a statistical improvement in pain, appetite loss and swallowing was observed over time. Conclusion: Although the outcomes of PCUE cancers remain dismal, the use of state of the art diagnostic modalities, careful case selection and modern radiotherapy techniques improved outcomes as compared with before in this exclusive analysis of PCUE cancers.